Prosecuting Conflict-Related Sexual Violence at the ICTY. Edited by Serge Brammertz and Michelle Jarvis. Oxford: Oxford University Press, 2016. 350 + xliii pages. - Wharton, Sara (Canadian Yearbook of International Law/Annuaire canadien de droit international, 2017)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0069005817000030/resource/name/firstPage-S0069005817000030a.jpg
Keywords: Sara Wharton